1999
DOI: 10.2307/1565575
|View full text |Cite
|
Sign up to set email alerts
|

Activity, Movement Patterns, and Home Range of the Yellow-Margined Box Turtle (Cuora flavomarginata) in Northern Taiwan

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Society for the Study of Amphibians and Reptiles is collaborating with JSTOR to digitize, preserve and extend access to Journal of Herpetology.ABSTRACT.-Estimates were made of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…Obtaining higher body temperature can have many benefits for turtles, such as enhanced digestive rates, increased fat mobilization and rates of follicle development (Avery, 1982;Congdon, 1989). Numerous authors have suggested that gravid female turtles are likely to maintain higher body temperature to accelerate egg development (Obbard and Brooks, 1979;Vogt, 1980;Lue and Chen, 1999). However, the higher basking frequency was observed only during nesting sea- Figure 5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obtaining higher body temperature can have many benefits for turtles, such as enhanced digestive rates, increased fat mobilization and rates of follicle development (Avery, 1982;Congdon, 1989). Numerous authors have suggested that gravid female turtles are likely to maintain higher body temperature to accelerate egg development (Obbard and Brooks, 1979;Vogt, 1980;Lue and Chen, 1999). However, the higher basking frequency was observed only during nesting sea- Figure 5.…”
Section: Discussionmentioning
confidence: 99%
“…The yellow-margined box turtle (Cuora flavomarginata) is an endangered species, inhabiting mesic forested habitats in low elevation of east Asia, including south-eastern China, Taiwan and southern Ryukyu Archipelagos of Japan (Ernst and Barbour, 1989;Zhao, 1998;Lue and Chen, 1999). It is threatened by overexploitation for pet and food, habitat loss and fragmentation (Zhao, 1998;Chen, Lin and Chang, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies measuring Terrapene HRs have reported wide variation in HR sizes within and between populations, possibly due to factors such as differences in habitat, demography, and the life history of individuals being tracked. The HR of the males of some terrestrial turtle species are typically larger than females [13,14], presumably because they are seeking females. In contrast, female HR of some species may be larger (e.g., [15]), which is perhaps because of extended excursions for oviposition.…”
Section: Introductionmentioning
confidence: 99%
“…In Taiwan, the turtle is found within and in the vicinity of the primary and well-developed secondary forests (Chen and Lue 1999). Based on the results of mark-recapture and radio tracking, Lue and Chen (1999) reported that a northern Taiwan population exhibits distinct seasonal movements and that the patterns of the movements differ remarkably between sexes. Female C. flavomarginata tended to maintain higher shell surface temperature during the nesting season (May to July).…”
Section: 4mentioning
confidence: 99%